Paying attention to children in a changing health care system : summaries of workshops (National Academy Press, 1996)
America's health care system is being reshaped by a variety of market-driven changes, and states are emerging as the major governmental influence on health care policy. Amid these changes, the health and well-being of children can slip from view. Although most children are fundamentally healthy, they require health care that emphasizes preventive services, such as immunizations and regular monitoring of physical and psychosocial growth and development. This volume takes a broad look at access and quality of care for pregnant women, children, and mothers. Among the issues addressed are the scope of benefits available under various health care reform efforts and services for special-needs children under managed care.